Effect of migrant parents' bodyweight perception on children's body bodyweight: A longitudinal analysis of population cohort study - Susan Hartono; Theo Niyonsenga; Tom Cochrane; Yohannes Kinfu (Elsevier, 2023)
Children of migrants in Australia are disproportionally affected by overweight/obesity. Their parents, however, are likely to put little effort into lifestyle changes if unable to recognise their children's suboptimal bodyweight. We examined the potential impact of migrant parents' bodyweight perception on their children's bodyweight over time and whether the region-of-birth of parents and acculturation to the host nation's way of life moderated the relationship, as very little is known about these in the Australian context. We analysed a sample of 2046 children of migrant parents drawn from 8 waves of population-based cohort data, the Longitudinal Study of Australian Children, capturing their lived experience from ages 2 to 17. After controlling for child, parent, family, and neighbourhood factors influencing children's bodyweight, multilevel models showed higher children's bodyweight in subsequent waves if their parents perceived children's bodyweight as lower than their actual bodyweight (i.e., underestimation). However, the rate of increase in children's bodyweight attenuated over time. The effect of migrant parents' underestimation on children's subsequent bodyweight differed by region-of-birth, with higher children's bodyweight in successive waves if their parents were from the Americas, compared to migrant parents from North/West Europe. Parents' acculturation, however, did not have a discernible effect. Although migrant parents' bodyweight perception of their children's bodyweight status influenced children's bodyweight in subsequent waves, this factor was not enough to explain the extent of disparities in children's bodyweight observed in the Australian migrant population. Further research is needed to assess the effects of other types of perception (such as perceptions of healthy weight and physical exercise) on bodyweight disparities in children of migrants.